The formation of constitutional rule: The politics of Ottomanism between de jure and de facto (1908-1913) - Zeren, Barış. (Thesis (Ph.D.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2017., 2017)
The dissertation examines the functioning of Ottoman constitutional rule born in 1908 which aimed at forming a new body politic, an Ottoman nation, on the sociopolitical structure inherited from the "old regime.” As this Otto-manism, which was officially and publicly referred as "the unity of elements" (ittihad-ı anasır), was closely related with the promise of parliamentarianism and the rule of constitutional norms, the dissertation focuses on the legislative and administrative practices starting in Spring 1909 until the outbreak of the Balkan Wars. To this end, the study follows the enactment and application phases of cer-tain critical laws in creating such a national unification — the martial law and the law on the conscription of non-Muslims to the Ottoman army — with specific emphasis on Macedonian-Bulgarian and Hellenist political networks. Tracing the development of tensions and strategies among official and civil political actors in Istanbul and Rumelia evolving around these laws, the dis-sertation demonstrates deviations in the interpretation of the Kanun-ı Esasi by various representatives of sociopolitical factions, the heterogeneity of atti-tudes of central and local political actors, and the effective role of local strug-gles in the development of constitutional sovereignty.
Keywords: Constitutional history -- Turkey.; Constitutional law -- Turkey.